Applying international engineering alliance standards in design and quality assurance of the higher and intermediate vocational training - Aleksandr I. Chuchalin (Высшее образование в России)
The paper examines standards of International Engineering Alliance (IEA) oforganizations forming the agreed requirements for the competences of professional engineers and technologists (International Professional Engineers Agreement/EMF, APEC Engineer Register, International Engineering Technologists Agreement/ETMF) and organizations developing and applying the engineering education criteria in universities and colleges (Washington Accord, Sydney Accord, Dublin Accord). There are presented the results ofcompetence analysis of IEA standards, and given the recommendations on its application indesign and quality assurance of the educational programmes in higher and intermediate vocational education in engineering at universities and colleges of the Russian Federation.